2023
DOI: 10.1007/s10341-023-00892-x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological to Molecular Markers: Plant Genetic Diversity Studies in Walnut (Juglans regia L.)—A Review

Abstract: Persian walnut populations have tremendous morphological and allelic diversity in their germplasm due to heavy outcrossing and years of seed multiplication. These variations are assessed by morphological, cytological, biochemical and molecular markers. Various researchers have used different tree, foliage, flower, nut, and kernel traits to evaluate morphological/phenotypic diversity. In walnut, morphological indices are considered the first to describe and classify the germplasm, but the environment influences… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 186 publications
0
3
0
Order By: Relevance
“…Nevertheless, the outcomes of our study are consistent with prior investigations into genetic diversity among walnut genotypes using SSR markers. It is important to acknowledge that the genetic and phylogenetic distances among the genotypes can also influence the level of polymorphism detected by SSR markers, particularly owing to the outcrossing nature of walnuts [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the outcomes of our study are consistent with prior investigations into genetic diversity among walnut genotypes using SSR markers. It is important to acknowledge that the genetic and phylogenetic distances among the genotypes can also influence the level of polymorphism detected by SSR markers, particularly owing to the outcrossing nature of walnuts [26].…”
Section: Discussionmentioning
confidence: 99%
“…Also, we observed that the average PIC value was higher when compared to the previously mentioned studies. These differences in PIC values among studies may arise from the utilization of distinct SSR markers or from the origins of samples, which could encompass considerably more diverse regions, potentially spanning different continents [26]. Notably, the Eurasia region, which includes Greece, has been recognized for its notably high levels of genetic diversity in walnuts [57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation